Is digital crime victimization increasing in Iceland – may the Me-too movement influence how victimization is experienced - Helgi Gunnlaugsson; Jónas Orri Jónasson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The first Icelandic study of digital crime victimization was conducted in 2016. According to the results, approximately 13 % of respondents reported digital victimization during the three years prior to the survey. Slander and consumer fraud were the most common types of victimization. Respondents between the ages of 30 to 44 were most likely to have been victimized. In 2018, the survey was repeated using the same questionnaire. As before, the survey was conducted online in cooperation with the Social Sciences Research Institute and solicited information from a sample of circa 2,000 respondents representative of the Icelandic population ages 18 years and older. Approximately 20 % reported a digital victimization in 2018. This suggests a significant increase in victimization since 2016. The increase was most notable in regards to the sexual harassment of women. It is contended that the MeToo Movement of 2017 may have had an impact on the experiences reported by women in 2018. Abstract Den første islandske undersøgelse, der fokuserede på kriminel krænkelse over internettet, blev udført i 2016. Ifølge resultaterne rapporterede ca. 13 % af respondenterne, at de inden for de seneste tre år forud for undersøgelsen havde været udsat for krænkelse over internettet. De mest almindelige former for krænklse var bagtalelse og forbrugerbedrageri. Respondenter i aldersgruppen 30-44 år viste sig at være mest udsatte. Undersøgelsen blev gentaget i 2018, med anvendelse af det samme skema som i 2016. Undersøgelsen blev også denne gang foretaget over nettet i samarbejde med centret for socialvidenskabelig forskning og udsendt til ca. 2000 deltagere, der afspejlede den islandske befolkning over 18 år. Ser vi en øgning i kriminel forulempelse over nettet? Ser vi andre former for forulempelse end i 2016? Har Me-Too bevægelse i Island haft nogen indflydelse på ofrenes oplevelse af at være krænket?